2017
DOI: 10.1515/corrrev-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effect of underpotential deposition of metallic cations on aqueous corrosion of metals

Abstract: Abstract:The experimental results reported so far for the inhibition effect of underpotential deposition (UPD) of metallic cations on aqueous corrosion of metals are criticized and discussed based on the prerequisite for UPD. The inhibition effect of Pb 2+ , Cd 2+ , Zn 2+ or Mn 2+ on hydrogen evolution or hydrogen absorption on Armco iron or various steels is classified into three potential regions: bulk deposition, UPD and adsorption of metallic cations without discharging. Moreover, the inhibition effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…As mentioned above and the results obtained from the polarization method, we can suggest the following explanation (Fig. 6) that at potentials E < E eq Pb 2+ /Pb , the electrodeposition of bulk lead phase on iron occurs, indicated by the limiting diffusion-controlled value for lead deposition [46], at potentials E eq Pb 2+ /Pb < E < E eq Pb 2+ /Pb + ΔE UPD , where ∆E UPD is the UPD potential window [44], the peak that appeared may be due to the effect of underpotential deposition (UPD) of Pb 2+ , then at potentials E Pb 2+ ∕Pb + ΔE UPD < E , the decreases in cathodic and anodic currents are mainly due to the adsorption of Pb 2+ .…”
Section: Electrochemical Measurementssupporting
confidence: 59%
See 2 more Smart Citations
“…As mentioned above and the results obtained from the polarization method, we can suggest the following explanation (Fig. 6) that at potentials E < E eq Pb 2+ /Pb , the electrodeposition of bulk lead phase on iron occurs, indicated by the limiting diffusion-controlled value for lead deposition [46], at potentials E eq Pb 2+ /Pb < E < E eq Pb 2+ /Pb + ΔE UPD , where ∆E UPD is the UPD potential window [44], the peak that appeared may be due to the effect of underpotential deposition (UPD) of Pb 2+ , then at potentials E Pb 2+ ∕Pb + ΔE UPD < E , the decreases in cathodic and anodic currents are mainly due to the adsorption of Pb 2+ .…”
Section: Electrochemical Measurementssupporting
confidence: 59%
“…The results showed that the coverage of Me-adsorbate on the metal surface by the underpotential deposition of Me Z+ is the main mechanism that diminishes the effect of an aggressive environment. Masahiro Seo [44] also reported experimental results of the inhibition effect of bulk deposition, UPD, and adsorption of metal cations on the corrosion of different metals. Generally, in our case, as demonstrated in the polarization and EIS methods, a remarkable increase in charge transfer resistance is probably due to the mechanisms of bulk deposition, UPD and adsorption of lead ions, which decrease the cathodic and anodic current densities by inhibition of charge transfer hydrogen evolution and active iron dissolution process, respectively.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cyclic voltammetry and in situ X-ray absorption spectroscopy (XAS), they observed that the anodic dissolution of the Ni substrate was concealed by the Pb-UPD 18,19 and Sn-UPD, 20,21 while the dissolution of the Fe and Fe-Ni alloy substrates was suppressed by Pb-UPD. 22 Subsequently, Seo discussed the possibility of Sn-UPD on iron and steels in a review article, 23 citing studies that reported the inhibition effect of Sn 2+ on the corrosion of iron and steels. Abdel-Aal et al suggested that the cathodic reaction on iron and carbon steel was inhibited by the UPD of Sn adatoms in carboxylic acid solutions; 17 however, no studies have discussed the suppression mechanism of Sn 2+ on the anodic dissolution of iron and steels from the viewpoint of UPD.…”
mentioning
confidence: 99%